2005
DOI: 10.1021/la051766l
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitive Properties and Surface Morphology of a Group of Heterocyclic Diazoles as Inhibitors for Acidic Iron Corrosion

Abstract: The heterocyclic diazoles 3-amino-1H-isoindole, indazole, imidazole, 4-bromoimidazole, 4-methylimidazole, pyrazole, 4-nitropyrazole, and 4-sulfopyrazole were investigated as corrosion inhibitors of iron in 1 M HCl using ac and dc techniques. The polarization curves showed a decrease in corrosion current for the inhibitor-containing solution. Impedance spectra demonstrate that the charge-transfer resistance in the presence of these inhibitors was greater than in inhibitor-free solution, except for 4-nitropyrazo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
81
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 198 publications
(82 citation statements)
references
References 67 publications
1
81
0
Order By: Relevance
“…[27]. Finally, the small peak may be assigned to the oxygen atom of adsorbed water with characteristic binding energy of 533.1 ± 0.2 eV [28].…”
Section: Structural Characterizationsmentioning
confidence: 97%
“…[27]. Finally, the small peak may be assigned to the oxygen atom of adsorbed water with characteristic binding energy of 533.1 ± 0.2 eV [28].…”
Section: Structural Characterizationsmentioning
confidence: 97%
“…The first two peaks correspond to the binding energy of the O 2-and OH -ions [45], in agreement with the presence of the iron oxide/hydroxide layer as detected in the Fe 2p 3/2 spectrum. The third peak at 532.7 eV may be assigned to oxygen of adsorbed water [46]. However, it is not possible to separate contributions of organic oxygen (O in carbonyl) since O 1s signal [47].…”
Section: Isotherm and Surface Studiesmentioning
confidence: 99%
“…The Xray photoelectron spectra of iron and its oxides is well known. 6,31 Due to unpaired electrons in the valence band, iron compounds show a complex structure related to the multiplet splitting. 32 The center of main Fe 2p 3/2 peak in metallic iron is located at binding energy, E b , 706.8 eV, whereas the second peak of lower intensity is located at 711.4 eV.…”
Section: 2 Chemical Speciationmentioning
confidence: 99%
“…Heterocyclic diazoles were also shown to be good inhibitors for iron in 1 M HCl. 6 Three types of iron species were identified on the inhibited surface: FeOOH, Fe 2 O 3 and Fe 3 O 4 . It was suggested that good inhibition agent should form an insoluble complex or surface species with low hydroxide content.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation